Harnessing the Potential of Multiomics Studies for Precision Medicine in Infectious Disease. (25th September 2021) - Ward, Rebecca A; Aghaeepour, Nima; Bhattacharyya, Roby P; Clish, Clary B; Gaudillière, Brice; Hacohen, Nir; Mansour, Michael K; Mudd, Philip A; Pasupneti, Shravani; Presti, Rachel M; Rhee, Eugene P; Sen, Pritha; et al.
Abstract: The field of infectious diseases currently takes a reactive approach and treats infections as they present in patients. Although certain populations are known to be at greater risk of developing infection (eg, immunocompromised), we lack a systems approach to define the true risk of future infection for a patient. Guided by impressive gains in "omics" technologies, future strategies to infectious diseases should take a precision approach to infection through identification of patients at intermediate and high-risk of infection and deploy targeted preventative measures (ie, prophylaxis). The advances of high-throughput immune profiling by multiomics approaches (ie, transcriptomics, epigenomics, metabolomics, proteomics) hold the promise to identify patients at increased risk of infection and enable risk-stratifying approaches to be applied in the clinic. Integration of patient-specific data using machine learning improves the effectiveness of prediction, providing the necessary technologies needed to propel the field of infectious diseases medicine into the era of personalized medicine. Abstract : Translational systems immunology approaches to infectious diseases will enable the switch from reactive to precision treatment of patients, which will improve clinical outcomes while reducing the use of prophylactic antibiotics and incidence of infection in high-risk individuals.